Effectiveness of Insecticide–Surfactant Combinations Against Thrips palmi on Eggplant - Lida Nurochmatusadiah; Anwar Fadlullah; Deden (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2026)
Eggplant (Solanum melongena L.) is an important horticultural crop in Indonesia; however, its productivity is frequently constrained by thrips infestation (Thrips palmi). This study aimed to evaluate the effectiveness of combinations of insecticide active ingredients and Ronstick surfactant in reducing the intensity of T. palmi attacks on eggplant plants. The research was conducted in Ender Village, Pangenan District, Cirebon Regency, from May to August 2025 using a Randomized Block Design with seven treatments and three replications. Treatments consisted of abamectin, dinotefuran, and their combinations, each applied with Ronstick surfactant at concentrations of 1–2 ml/L, and a control without insecticide. The results showed that insecticide–surfactant combinations significantly reduced thrips population and attack intensity compared to the control. The combination of abamectin + dinotefuran with surfactant at 2 ml/L was the most effective treatment. These findings indicate that appropriate insecticide–surfactant combinations can enhance thrips control efficiency while supporting more rational insecticide use.